2020
DOI: 10.1155/2020/5753623
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic Acid Promotes Browning of 3T3-L1 Adipocytes via p38 MAPK/CREB Pathway

Abstract: Sinapic acid is a plant-derived phenolic compound, which acts as an antioxidant, anticancer, and anti-inflammatory agent. Although sinapic acid is valuable in a variety of therapeutic applications, its role in the improvement of obesity-related metabolic disease is relatively unexplored. Brown-like adipocytes (beige adipocytes) are characterized by a high concentration of mitochondria and high expression of uncoupling protein 1 (UCP1), which has specific functions in energy expenditure and thermogenesis. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Some studies confirmed the positive role of MAPK pathway in browning of adipocytes in 3T3-L1 cells. ( Bae and Kim, 2020 ). Our present study also supported that the augmentation of browning by SFN treatment is involved with the activation of MAPK pathway at the late period of adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies confirmed the positive role of MAPK pathway in browning of adipocytes in 3T3-L1 cells. ( Bae and Kim, 2020 ). Our present study also supported that the augmentation of browning by SFN treatment is involved with the activation of MAPK pathway at the late period of adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…WAT browning in mice is stimulated by overexpression of zinc alpha 2 glycoprotein (ZAG) ( 169 ), and in 3T3-L1 white adipocytes ZAG increases the expression of brown fat markers and induces mitochondrial biogenesis via PKA and p38 signaling ( 170 ). The naturally occurring compound cryptotanshinone promotes brown-tissue and beige-cell markers by activating AMPK, p38, and Smad1/5 ( 58 ), whereas sinapic acid achieves the same effect via AMPK, p38, and PGC1 α ( 171 ). Treatment with the non-steroidal anti-inflammatory drug ketoprofen induces browning in 3T3-L1 cells and inguinal WAT, increasing mitochondrial biogenesis through an intricate signaling pathway involving p38, mTORC1, and COX activation ( 172 ).…”
Section: P38 and White Adipose Tissue Browningmentioning
confidence: 99%
“…As the biological activities of sinapic acid and its derivatives have been discovered, they have been used in various fields, such as the pharmaceutical industry, food, beverages, and cosmetics (Chen, 2016). Some studies have shown that sinapic acid has many beneficial properties, such as anti‐inflammatory properties (Bin Jardan et al, 2020; Lan et al, 2021; Lee, 2018; Qian et al, 2020), antioxidant (Yang et al, 2019), antihyperuricemic (Ishaq et al, 2020), anticancer (Eroglu et al, 2018; Zhao et al, 2021), and lipid homeostasis regulation (Wu et al, 2021) and promotes lipolysis (Bae & Kim, 2020; Hossain et al, 2020). However, the effects of sinapic acid on HFD‐induced lipid metabolism and its mechanism of action have been less reported.…”
Section: Introductionmentioning
confidence: 99%